2013
DOI: 10.2147/rmhp.s55305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk-scoring algorithm to forecast scrub typhus severity

Abstract: PurposeTo develop a simple risk-scoring system to forecast scrub typhus severity.Patients and methodsSeven years’ retrospective data of patients diagnosed with scrub typhus from two university-affiliated hospitals in the north of Thailand were analyzed. Patients were categorized into three severity groups: nonsevere, severe, and dead. Predictors for severity were analyzed under multivariable ordinal continuation ratio logistic regression. Significant coefficients were transformed into item score and summed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…[ 3 ] Predictors of severity of scrub typhus and dengue and scoring systems to identify severe illness have been described by many researchers in the past. [ 15 16 17 18 ] A systematic review identified 15 studies that have examined the differences in clinical and laboratory features between dengue and other febrile illnesses. [ 19 ] Chrispal et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Predictors of severity of scrub typhus and dengue and scoring systems to identify severe illness have been described by many researchers in the past. [ 15 16 17 18 ] A systematic review identified 15 studies that have examined the differences in clinical and laboratory features between dengue and other febrile illnesses. [ 19 ] Chrispal et al .…”
Section: Discussionmentioning
confidence: 99%
“…The overall proportion of correct classifications was somewhat lower (61.0% vs 68.3%), but overestimation was higher (27.0% vs 25.8%), which may be considered more beneficial to the patients. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Data were retrieved retrospectively from the medical files of scrub typhus patients. The criteria for inclusion were similar to those used in the previous study 17 and were based on history of disease exposure and presentation with acute fever and at least one of the following signs and symptoms: myalgia, headache, conjunctival injection, cough, profuse sweating, maculopapular rash, and/or lymphadenopathy accompanied by the presence of eschar, and/or a positive immuno-chromatographic test for scrub typhus. 18…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations